Balancing Histone Deacetylase (HDAC) Inhibition and Drug‐likeness: Biological and Physicochemical Evaluation of Class I Selective HDAC Inhibitors. (18th February 2022) - Schäker‐Hübner, Linda; Haschemi, Reza; Büch, Thomas; Kraft, Fabian B.; Brumme, Birke; Schöler, Andrea; Jenke, Robert; Meiler, Jens; Aigner, Achim; Bendas, Gerd; Hansen, Finn K.
Abstract: Herein we report the structure‐activity and structure‐physicochemical property relationships of a series of class I selective ortho ‐aminoanilides targeting the "foot‐pocket" in HDAC1&2. To balance the structural benefits and the physicochemical disadvantages of these substances, we started with a set of HDACi related to tacedinaline (CI‐994) and evaluated their solubility, lipophilicity (log D7.4 ) and inhibition of selected HDAC isoforms. Subsequently, we selected the most promising "capless" HDACi and transferred its ZBG to our previously published scaffold featuring a peptoid‐based cap group. The resulting hit compound 10 c (LSH‐A54) showed favorable physicochemical properties and is a potent, selective HDAC1/2 inhibitor. The following evaluation of its slow binding properties revealed that LSH‐A54 binds tightly to HDAC1 in an induced‐fit mechanism. The potent HDAC1/2 inhibitory properties were reflected by attenuated cell migration in a modified wound healing assay and reduced cell viability in a clonogenic survival assay in selected breast cancer cell lines. Abstract : In a fragment‐like approach we selected a "foot pocket" unit (FPU) with favorable properties and transferred this FPU to our peptoid‐based HDACi scaffold (middle). The subsequently selected hit‐compound 10 c (LSH‐A54 ) is a potent, slow‐binding inhibitor of HDAC1&2 with good selectivity over HDAC3 and shows a favorable physicochemical profile. Additional biological evaluations revealed promising anti‐cancer properties.